Students' Perceptions of Face-to-Face Learning during the Covid-19 Pandemic at SMAIT Al-Fityan School Gowa - Akib, Haedar Akib; Qalsum, Witry; Nasrullah, Muh (Universitas Negeri Makassar, 2023)
The implementation of Face-to-Face Learning, which is the government's new policy in the midst of the pandemic, gives new hope to students. After more than a year of online learning from home, the government issued regulations regarding limited Face-to-Face Learning plans. This research aims to determine the description of students' perceptions of Face-to-Face Learning during the COVID-19 pandemic at SMAIT Al-Fityan School Gowa. This research uses a quantitative research approach with a descriptive research type. The total population in this study was 153 people, then the researchers drew a sample of 50%, namely 77 people, using a simple random sampling technique. Data collection was carried out using several techniques including questionnaires, interviews, and documentation. Meanwhile, the data analysis technique used is percentage analysis. The research results show that students' perceptions of Face-to-Face Learning (PTM) during the COVID-19 pandemic are classified as very effective in terms of indicators for managing learning implementation, communication processes, student responses, and learning activities. To achieve a good perception of Face-to-Face Learning (PTM) during the COVID-19 pandemic, teachers make efforts to improve the learning process such as strategies, approaches, and learning methods in order to create a more lively and meaningful classroom atmosphere